A Systematic Review of Training Methods That May Improve Selective Voluntary Motor Control in Children With Spastic Cerebral Palsy - Fahr, Annina; Keller, Jeffrey W.; van Hedel, Hubertus J. A. (Frontiers in Neurology, 2020)
Background: Impaired selective voluntary motor control is defined as ‘the reduced ability to isolate the activation of muscle in response to demands of a voluntary posture or movement.’ It is a negative motor sign of an upper motor neuron lesion. Objective: This paper reviews interventions that may improve selective motor control in children and youths with spastic cerebral palsy. The aim was to systematically evaluate the methodological quality and formulate the level of evidence from controlled studies. Methods: Six databases (Scopus, Web of Science, PubMed, Embase, MEDLINE, and CINAHL) were searched with predefined search terms for population, interventions, and outcomes. Two reviewers independently completed study selection and ratings of methodological quality and risk of bias. Evidence was summarized in a best evidence synthesis. Results: Twenty-three studies from initially 2634 papers were included. The interventions showed a wide variety of approaches, such as constraint-induced movement therapy (CIMT), electrical stimulation, robot-assisted therapy, and functional training. The evidence synthesis revealed conflicting evidence for CIMT, robot-assisted rehabilitation and mirror therapy for the upper extremities in children with cerebral palsy. Conclusions: Final recommendations are difficult due to heterogeneity of the reviewed studies. Studies that include both an intervention and an outcome that specifically focus on selective voluntary motor control are needed to determine the most effective therapy.